A method for simultaneously measuring friction and gap at metal–lubricant interface by combined use of atomic force microscopy and line-and-space patterned metal films - Yamashita, Naoki; Hirayama, Tomoko (Frontiers in Mechanical Engineering, 2024)
In boundary lubrication, adsorbed molecular films formed by lubricant additives on the metal surfaces of sliding parts effectively reduce friction and wear. A method is presented for simultaneously measuring friction and the gap at a metal–lubricant interface under boundary lubrication conditions using atomic force microscopy. In this method, line-and-space patterns are microfabricated in Cu films on Si substrates, and the gap is evaluated from the step height change when scanning in base oil and in base oil with an additive. Neutron reflectometry showed that whereas both stearic acid and stearyl alcohol formed molecular film about 2 nm thick on Cu film in a static state, the gap increased only with stearic acid due to maintaining a molecular film on the Cu film. This demonstrates the feasibility of the proposed method as means for visualizing the gap and shows that there is a difference between the two additives in their film-forming ability in a static state and their durability against friction. The proposed method for simultaneously measuring friction and the gap at a metal–lubricant interface is thus an effective way to investigate the tribological performance of additives under boundary lubrication conditions.